Are Helicobacter Pylori and Benign Prostatic Hyperplasia Related, and If So, How? - Verit, Ayhan; Yüksel, Özgür Haki; Kivrak, Mithat; Yazicilar, Hanife Aydin; Özbay, Nurver; Uruç, Fatih (Urology Journal, 2015)
Purpose: Although many virulence factors have been defined for Helicobacter pylori (HP), vacuolating cytotoxin A (VacA) is known to be associated with apoptosis, the cag pathogenicity island protein (Cag-PAI),and growth factors. Both apoptosis and growth factors are thought to be related to the etiology of benign prostatic hyperplasia(BPH). Additionally, the relation between atherosclerosis-BPH and atherosclerosis-HP has also been reported in a limited number of studies. The aim of this pioneering study was to investigate the presence of HP in BPH patients who had undergone transurethral resection of prostate (TURP) and to discuss the potential pathophysiologic effects of HP on BPH. Materials and Methods: A total of 113 cases who underwent TURP due to infravesical obstruction due to BPH were included in thestudy. Preoperatively, parameters including, age, height, body weight, body mass index (BMI), prostate specific antigen (PSA), prostate volume (PVo), maximum urinary flow rate (Qmax), fasting plasma insulin, and International Prostate Symptom Score (IPSS)values were evaluated. The presence of HP was investigated in the prostate specimens with real-time polymerase chain reaction (RT-PCR) method. Postoperatively, histopathological evidence of chronic prostatitis (hCP) was also analyzed. Results: HP was detected in 1.8% (n=2) of the participants. Additionally, hCP was observed in 58.4% (n=66) of the 113 patients. The demographic and clinical parameters confirmed the presence of BPH disease. Conclusion: Although BPH is a common disease, its physiologic etiology mechanisms are not clear. Based on our pilot study, despite its gastric location, we believe that HP should be considered in cases with clinical BPHbecause HP induces apoptosis and alterations in the equilibrium between apoptosis and local growth factorsin addition to its recently demonstrated extragastric effects mediated via the atherosclerotic pathway. Although our uncontrolled pioneer study was not designed to investigate the pathophysiologic mechanism, the isolation of HP from prostatic adenomasuggests the need for further well-designed studies on this topic.